Survival of sharp force trauma in burnt bones: effects of environmental factors - Vachirawongsakorn, Vijarn; Márquez-Grant, Nicholas; Painter, Jonathan (Springer, 2023)
This study investigates how environmental variables, such as temperature and rainfall, affect previously induced cut marks on burnt bones. This research used non-serrated and serrated blade knives to inflict trauma on Sus scrofa ribs (n = 240). The bones were later burnt and left for 1 month in a taphonomic experimental facility. Qualitative and quantitative examinations were conducted using macroscopic and microscopic techniques to assess specific characteristics of the cut marks. Any changes to the dimension and morphology of the cut marks as well as their level of fragmentation were recorded. This study has led to three important outcomes: (1) identification of pre-existing cut marks is possible in reconstructed burnt bone fragments; (2) cut marks from different types of knife blades showed dissimilar responses to heat and the environment; and (3) specific environmental variables affect burnt bone fragmentation. These results have implications for trauma analysis on burnt remains in forensic anthropology casework.
Keywords: taphonomy; sharp-force trauma; forensic anthropology; human remains; burnt bone; cut marks